Example 1 :
x + [1/(x + 2)] = 4
Solution :
x + [1/(x + 2)] = 4
By taking the least common multiple, we get
x(x + 2)/(x + 2) + 1/(x + 2) = 4
[x(x + 2) + 1]/(x + 2) = 4
(x2 + 2x + 1)/(x + 2) = 4
By cross multiplication, we get
x2 + 2x + 1 = 4(x + 2)
x2 + 2x + 1 = 4x + 8
x2 + 2x + 1 – 4x – 8 = 0
x2 – 2x – 7 = 0
Since this quadratic equation is not factorable, we can solve it using quadratic formula.
x = [-b ± √(b2 – 4ac)]/2a
Here a = 1, b = -2 and c = -7
x = [-(-2) ± √(-2)2 – 4(1)(-7)]/2(1)
x = [2 ± √(4+28)]/2(1)
x = [2 ± √(32)]/2
x = [2 ±
4√2]/2
x = 2(1 ± 2√2)/2
x = 1 ± 2√2
So, the solution of x is 1 ± 2√2.
Example 2 :
3x – [4/(x + 1)] = 10
Solution :
3x - [4/(x + 1)] = 10
By taking the least common multiple, we get
3x(x + 1)/(x + 1) - 4/(x + 1) = 10
[3x(x + 1) - 4]/(x + 1) = 10
(3x2 + 3x - 4)/(x + 1) = 10
By cross multiplication, we get
3x2 + 3x - 4 = 10(x + 1)
3x2 + 3x - 4 = 10x + 10
3x2 + 3x - 4 – 10x – 10 = 0
3x2 – 7x – 14 = 0
This quadratic equation is not factorable. So, we have to use quadratic formula to solve the quadratic equation.
x = [-b ± √(b2 – 4ac)]/2a
Here a = 3, b = -7 and c = -14
x = [-(-7) ± √(-7)2 – 4(3)(-14)]/2(3)
x = [7 ± √(49 + 168)]/6
x = (7 ± √217)/6
So, the solution of x is (7 ± √217)/6
Example 3 :
(x + 2)/(x - 1) = 3x/(x + 1)
Solution :
(x + 2)/(x – 1) = 3x/(x + 1)
By cross multiplication, we get
(x + 2) (x + 1) = 3x(x – 1)
x2 + x + 2x + 2 = 3x2 – 3x
3x2 – 3x - x2 - x - 2x – 2 = 0
2x2 – 6x – 2 = 0
Dividing by 2, we get
x2 – 3x – 1 = 0
x = [-b ± √(b2 – 4ac)]/2a
Here a = 1, b = -3 and c = -1
x = [-(-3) ± √(-3)2 – 4(1)(-1)]/2(1)
x = [3 ± √(9 + 4)]/2
x = (3 ± √13)/2
So, the solution of x is (3 ± √13)/2
Find x in :
Example 4 :
Solution :
a)
Given BD || AE
<CBD = <CAE
<BCD = <ACE
By using AA theorem,
∆CBD ~ ∆CAE
Then, BD/AE = CD/CE
Here, BD = x m, AE = (x + 5) m,
CD = 6 m and CE = (x + 8) m
x/(x + 5) = 6/(x + 8)
By cross multiplication, we get
x(x + 8) = 6(x + 5)
x2 + 8x = 6x + 30
x2 + 2x – 30 = 0
So we have to find x value using the quadratic formula.
x = [-b ± √(b2 – 4ac)]/2a
Here a = 1, b = 2 and c = -30
x = [-(2) ± √(2)2 – 4(1)(-30)]/2(1)
x = [-2 ± √(4 + 120)]/2
x = (-2 ± √124)/2
x = (-2 ± 2√31)/2
x
= -1 ± √31
x = -1 + √31 and x = -1 - √31
So, the value of x is -1 + √31
b)
In right ∆PQR
The perpendicular drawn from the right angle, then the large triangle PQR is similar to the triangles PQS and QSR.
x(3x – 1) = (2x – 1)(2x – 1)
3x2 – x = 4x2 – 2x – 2x + 1
4x2 – 2x – 2x + 1 – 3x2 + x = 0
x2 – 3x + 1 = 0
x = [-b ± √(b2 – 4ac)]/2a
Here a = 1, b = -3 and c = 1
x = [-(-3) ± √(-3)2 – 4(1)(1)]/2(1)
x = [3 ± √(9 - 4)]/2
x = (3 ± √5)/2
x = (3 + √5)/2 and x = (3 - √5)/2
we are taking it a positive value.
So, the solution of x is (3 + √5)/2
Example 5 :
Two numbers have a sum of 4, and the sum of their reciprocals is 8. Find the numbers.
Solution :
Let the two numbers x and y.
x + y = 4 -----(1)
1/x + 1/y = 8 -----(2)
Considering equation (2), we have
1/x + 1/y = 8
(y + x)/xy = 8
y + x = 8xy
By using equation (1), we get
4 = 8xy
1 = 2xy
1 = 2x(4 – x)
1 = 8x – 2x2
2x2 – 8x + 1 = 0
Solving this quadratic equation using formula, we get
x = [-b ± √(b2 – 4ac)]/2a
Here a = 2, b = -8 and c = 1
x = [-(-8) ± √(-8)2 – 4(2)(1)]/2(2)
x = [8 ± √(64 - 8)]/4
x = (8 ± √56)/4
x = (8 ±
2√14)/4
x = (2 ±
1/2√14)
x = (2 + 1/2√14) and x = (2 – 1/2√14)
we are taking a positive value.
By applying x = (2 + 1/2√14) in equation (1), we get
x + y = 4
2 + 1/2√14 + y = 4
y = 4 – 2 – 1/2√14
y = 2 – 1/2√14
Then x = (2 + 1/2√14) then y = 2 – 1/2√14.
Kindly mail your feedback to v4formath@gmail.com
We always appreciate your feedback.
©All rights reserved. onlinemath4all.com
Feb 08, 25 10:15 PM
Feb 08, 25 10:13 PM
Feb 08, 25 10:09 PM